Thermodynamics and kinetics of core-shell versus appendage co-precipitation morphologies: An example in the Fe-Cu-Mn-Ni-Si system. (15th September 2018) - Shu, Shipeng; Wells, Peter B.; Almirall, Nathan; Odette, G. Robert; Morgan, Dane D.
Abstract: What determines precipitate morphologies in co-precipitating alloy systems? We focus on alloys of two precipitating phases, with precipitates of the fast-precipitating phase acting as heterogeneous nucleation sites for a second phase manifesting slower kinetics. We study a FeCuMnNiSi alloy using the combination of atom probe tomography and kinetic Monte Carlo simulations. It is shown that the interplay between interfacial and ordering energies, plus active diffusion paths, strongly affect the selection of core-shell verses appendage morphologies. Specifically, the ordering energy reduction of the MnNiSi phase heterogeneously nucleated on a pre-existing copper-rich precipitate exceeds the energy penalty of a predominantly Fe/Cu interface, leading to initial appendage, rather than core-shell, formation. Diffusion of Mn, Ni and Si around and through the Cu core towards the ordered phase results in subsequent appendage growth. We further show that in cases with higher primary precipitate interface energies and/or suppressed ordering, the core-shell morphology is favored. Graphical abstract: Image 1